2021
DOI: 10.1002/wnan.1702
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated‐platelet‐inspired nanomedicines for cancer therapy

Abstract: Platelets, with hemostasis and thrombosis activities, are one of the key components in the blood circulation. As a guard, they rapidly respond to any abnormal blood vessel injury signal and release their granules' contents, which induce their adhesion and aggregation on wound site for hemostasis. Recently, increasing evidence has indicated that platelets are critically involved in the growth and metastasis of cancer cells by releasing a variety of cytokines and chemokines to stimulate cancer cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 136 publications
0
17
0
Order By: Relevance
“…Platelets regulate thrombosis and hemostasis. Nevertheless, a few studies suggested that crosstalk between tumor cells and platelets facilitates cancer progression and metastasis ( 54 , 55 ). Tumorigenesis is accompanied by thrombosis and thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets regulate thrombosis and hemostasis. Nevertheless, a few studies suggested that crosstalk between tumor cells and platelets facilitates cancer progression and metastasis ( 54 , 55 ). Tumorigenesis is accompanied by thrombosis and thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nano-delivery systems have received extensive attention due to their ability to deliver drugs to targeting lesions ( Geranpayehvaghei et al, 2021 ). Therapeutic agents included small molecules and macromolecules such as proteins and nucleic acids.…”
Section: Application Of Biomimetic Exosomesmentioning
confidence: 99%
“…Several research groups in recent years have also explored an interesting strategy of coating anticancer drug loaded nanoparticles with lipid membrane extracted from platelets (a process termed biointerfacing), with the rationale that the some of the tumor‐interactive mechanisms of the platelets will be retained in the coated membrane to enable tumor‐targeted drug delivery. In this framework, platelet membrane‐coated nanoparticles have been used to deliver immune checkpoint inhibitors, chemotherapy drugs, and photothermal therapy agents to cancer, with promising results 108,109 . In another analogous approach, doxorubicin‐loaded nanoparticles were coated with platelet‐derived membrane as well as decorated with TNF‐related apoptosis‐inducing ligand, and these systems showed promising efficacy in tumor‐targeting and reducing metastasis 110 .…”
Section: Platelet‐inspired Nanomedicine Approaches For Treating Cancermentioning
confidence: 99%
“…In this framework, platelet membrane-coated nanoparticles have been used to deliver immune checkpoint inhibitors, chemotherapy drugs, and photothermal therapy agents to cancer, with promising results. 108,109 In another analogous approach, doxorubicin-loaded nanoparticles were coated with platelet-derived membrane as well as decorated with TNF-related apoptosis-inducing ligand, and these systems showed promising efficacy in tumor-targeting and reducing metastasis. 110 In another recent approach, detergent-treated platelets lacking adhesion and aggregation capabilities were shown to act as "platelet decoys" that can inhibit platelet arrest on matrix proteins in vitro and reduce tumor metastasis in mouse model in vivo.…”
Section: Pl Atele T-ins Pired Nanomedicine Approache S For Tre Ating ...mentioning
confidence: 99%